Prediction of Postprostatectomy Biochemical Recurrence Using Quantitative Ultrasound Shear Wave Elastography Imaging - Wei, Cheng; Zhang, Yilong; Malik, Hamza; Zhang, Xinyu; Alqahtani, Saeed; Upreti, Dilip; Szewczyk-Bieda, Magdalena; Lang, Stephen; Nabi, Ghulam (Frontiers in Oncology, 2019)
Objectives: To determine the prognostic significance of tissue stiffness measurement using transrectal ultrasound shear wave elastography in predicting biochemical recurrence following radical prostatectomy for clinically localized prostate cancer. Patients and Methods: eligible male patients with clinically localized prostate cancer and extraperitoneal laparoscopic radical prostatectomy between November 2013 and August 2017 were retrospectively selected. Information of potential biochemical recurrence predictors, including imaging (ultrasound shear wave elastography and Magnetic Resonance Imaging), clinicopathological characteristics, and pre-operative PSA levels were obtained. Recurrence-free survival (Kaplan-Meier curve) and a multivariate model were constructed using Cox regression analysis to evaluate the impact of shear wave elastography as a prognostic marker for biochemical recurrence. Results: patients experienced biochemical recurrence in an average of 26.3±16.3 months during their follow-up. A cut-off of 144.85 kPa for tissue stiffness measurement was estimated for recurrence status at follow-up with sensitivity of 74.4% and specificity of 61.7%, respectively (p<0.05). In univariate analysis, shear wave elastography performed well in all preoperative factors compared to biopsy Gleason Score, PSA and Magnetic Resonance Imaging; in multivariate analysis with postoperative pathological factors, shear wave elastography was statistically significant in predicting postoperative biochemical recurrence, which improved the C-index of predictive nomogram significantly (0.74 vs. 0.70, p<0.05). Conclusions: The study revealed that quantitative ultrasound shear wave elastography measured tissue stiffness was a significant imaging marker that enhanced the predictive ability with other clinical and histopathological factors in prognosticating postoperative biochemical recurrence following radical prostatectomy for clinically localized prostate cancer.